Association of complex congenital heart disease and adquired cardiopathy - Pedro Martínez Losas; Teresa Nogales Romo; Elena Fortuny; David Vivas; Ada Laubele (ECIMED, 2014)
Superior sinus venosus type atrial septal defect accounts for about 5% of interatrial septum defects. In most cases, this deficiency is associated with an anomalous pulmonary venous return that leads to an additional left-to-right shunt. Herein, we present a very characteristic case of an asymptomatic adult patient with this congenital heart disease combined with an anomalous drainage of the pulmonary veins, who also shows persistent left superior vena cava, together with atherosclerotic lesions in coronary and peripheral arteries as incidental findings.